2015
DOI: 10.1002/chin.201530241
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Caesaljaponins A and B: New Cassane‐Type Furanoditerpenoids from the Seeds of Caesalpinia decapetala var. japonica

Abstract: Caesaljaponins A and B: New Cassane-Type Furanoditerpenoids from the Seeds of Caesalpinia decapetala var. japonica -[isolation, structure and absolute stereochemistry]. -(KAMIKAWA, S.; OHTA, E.; OHTA*, S.; Helv. Chim. Acta 98 (2015) 3, 336-342, http://dx.doi.org/10.1002/hlca.201400170 ; Grad. Sch. Biosphere Sci., Hiroshima Univ., Higashi-Hiroshima 739, Japan; Eng.) -A. Forchert 30-241

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…1 isolated from the EtOAc-soluble fraction of the intact seeds of Caesalpinia decapetala are given in Fig. 2 [2] , [3] , [4] . The HPLC profiles of the furanoditerpenoids 5 – 11 shown in Fig.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…1 isolated from the EtOAc-soluble fraction of the intact seeds of Caesalpinia decapetala are given in Fig. 2 [2] , [3] , [4] . The HPLC profiles of the furanoditerpenoids 5 – 11 shown in Fig.…”
Section: Datamentioning
confidence: 99%
“… The data presented here are related to the research paper entitled “Hydroxylated furanoditerpenoids from the pupal case produced by the bruchid beetle Sulcobruchus sauteri inside the seed of Caesalpinia decapetala ” (Akihara et al, 2018) [1] . In this data article, we provide high-performance liquid chromatography (HPLC) profiles of seven undescribed hydroxylated furanoditerpenoids, caesalsauteolide, 2-hydroxycaesaljapin, 2,7-dihydroxycaesaljapin, 2-hydroxycaesalacetal, caesalsauterol, 6-acetylcaesalsauterol, norcaesalsauterol isolated from the pupal cases produced by Sulcobruchus sauteri and four known compounds, caesaljaponin A (Kamikawa et al, 2015) [2] , caesaljaponin B (Kamikawa et al, 2015) [2] , caesalacetal (Kamikawa et al, 2016) [3] , and caesaljapin (Kamikawa et al, 2016; Ogawa et al, 1992) [3] , [4] isolated from the cotyledons of the intact seeds of Caesalpinia decapetala . Besides, 1D NMR, 2D NMR, and HRESIFTMS data of the seven undescribed furanoditerpenoids are also presented.…”
mentioning
confidence: 99%
“…Ficus nipponica is a wild evergreen climbing plant native to Southeast Asia, bearing a fig‐like fruit with a diameter of 10 mm. During a continuing search for biologically active compounds from plants, we found that the crude MeOH extract of the fruits of F . nipponica showed antibacterial activity against Bacillus subtilis .…”
Section: Introductionmentioning
confidence: 99%
“…Ficus nipponica is a wild evergreen climbing plant native to Southeast Asia, bearing a figlike fruit with a diameter of 10 mm. During a continuing search for biologically active compounds from plants, [10] [11] we found that the crude MeOH extract of the fruits of F. nipponica showed antibacterial activity against Bacillus subtilis. Bioassay-guided fractionation of the crude extract led to the isolation of two new prenylated ortho-dihydroxycoumarins, designated as fipsomin (1) and fipsotwin (2), together with a known prenylated coumarin, apigravin (3).…”
Section: Introductionmentioning
confidence: 99%